Factors associated with the decision to receive bivalent COVID-19 booster vaccination among health care personnel - Nicholas M. Mohr; Ian D. Plumb; Eliezer Santos León; Karisa K. Harland; Anusha Krishnadasan; Utsav Nandi; Karin F. Hoth; Howard A. Smithline; David A. Talan (Human Vaccines & Immunotherapeutics, 2023)
ABSTRACTCOVID-19 vaccination is effective at reducing SARS-CoV-2 complications, but uptake has been low. Our objective in this study was to compare the importance of factors reported to influence the decision to receive a bivalent COVID-19 booster vaccine among health care personnel (HCP) tested for SARS-CoV-2 between October 2022 and April 2023 in a 20-hospital vaccine effectiveness study in the United States (n = 1656). Compared with those who had not received the booster, the factors most likely to be reported to be important were concerns about contracting COVID-19 (84.0% of those who had received the bivalent booster vs. 47.5% of those who had not, difference 36.6% points (PP), 95% confidence interval [CI] 32.1 to 41.1%), spreading infection to family members (89.2% vs. 62.8%, difference 26.3 PP, 95% CI 22.3 to 30.4%), and spreading infection to colleagues at work (85.5% vs. 59.4%, difference 26.1 PP, 95% CI 21.7 to 30.5%). HCP who had received the booster more frequently cited the primary literature (61.7% vs. 31.8%, difference 29.9 PP, 95% CI 24.6 to 35.2%) and employer recommendations (48.3% vs. 29.8%, difference 18.5 PP, 95% CI 13.2 to 23.9%) as influencing their decision. This analysis provides insight into factors for targeting future vaccine messaging.